Tool wear and hole quality in drilling of CFRP/AA7075 stacks with DLC and nanocomposite TiAlN coated tools. (December 2017) - D'Orazio, A.; El Mehtedi, M.; Forcellese, A.; Nardinocchi, A.; Simoncini, M.
Graphical abstract: Highlights: Drilling of CFRP/AA7075 stacks was performed using drills coated with DLC and TiAlN. The DLC coated drill underwent a much lower wear than TiAlN coated one. Delamination was much less pronounced using the DLC coated tool. The exit hole diameter of the stack is much lower than the entry hole one. Relationships among wear, thrust force, delamination and hole diameter were found. Abstract: Drilling of multi-material stacks, constituted by two laminates in carbon fiber reinforced plastic and a core plate in AA7075, was widely investigated. Experiments were performed on a 5-axis CNC machining center, equipped with a dynamometer for the thrust force measurement, using different twist drills coated with DLC and nanocomposite TiAlN. Each hole, 6.8 mm in diameter, was obtained with a chip removal cycle involving two passes spaced by a back motion. Optical and scanning electron microscopy techniques were used to quantify tool wear and delamination of composite layers. Finally, hole diameter in the different layers of composite/aluminum stack was measured by means of a coordinate measuring machine. The analysis of experimental results showed that the main wear mechanisms operating during drilling of stacks with the DLC coated drill are chipping, edge rounding and abrasion, while wear is mainly affected by abrasion with the nanocomposite TiAlN coated tool, even though adhesion of AA7075 particles on the rake surface also occurs. The evolution of flank wear with number of holes showed that the DLC coated drill underwent a much lower wear than the TiAlN coated one. Thrust force on both CFRP and AA7075 exhibited an increase with number of holes. Delamination of composite layer was already present in drilling performed with the wear free tool. However, a growth in delamination with number of holes was observed. Progression of hole diameter with number of holes, in the three different layers of multi-material stack, showed that diameter decreases with rising number of holes. Finally, systematic correlations between tool wear, thrust force, hole diameter and delamination factor were defined. Owing to the plot characteristics, the third-degree polynomial regression was found adequate to model interactions among the process results.